Depressed antithrombin III biological activity in opiate addicts. Issue 9 (September 1984) - Ceriello, A; Dello Russo, P; Curcio, F; Tirelli, A; Giugliano, D
Abstract : Antithrombin III activity was significantly decreased in opiate addicts, but no difference was found between addict and control groups in antithrombin III plasma concentration. Moreover, glycosylated haemoglobin concentration was increased in opiate addicts, but no correlation between glycosylated haemoglobin and antithrombin III activity was found. These data show that in opiate addicts there is depressed biological activity of antithrombin III. Further characterisation of the molecular changes in antithrombin III in addicts is needed to establish whether the impaired activity is affected by altered glucose metabolism.